Visual outcomes of laser vision correction in eyes with preoperative amblyopia. Issue 3 (March 2017) - Sorkin, Nir; Varssano, David; Smadja, David; Klein, Ainat; Mimouni, Michael; Rosenblatt, Amir
Abstract : Purpose : To evaluate the visual outcomes of photorefractive keratectomy (PRK) and laser in situ keratomileusis (LASIK) in amblyopic eyes. Setting : Care Vision Refractive Clinic, Tel Aviv, Israel. Design : Retrospective case series. Methods : Amblyopic eyes of patients with a preoperative corrected distance visual acuity (CDVA) of 20/33 or worse had PRK or LASIK. Postoperative visual outcomes (uncorrected distance visual acuity, CDVA) and correlations with age, preoperative CDVA, refractive error type, astigmatism grade, procedure type, laser suite model, amblyopia grade, and amblyopia type were analyzed. Results : This study evaluated 327 eyes (327 patients). The CDVA improved more than 1, 2, and 3 Snellen lines in 147 eyes (45.0%), 75 eyes (22.9%), and 32 eyes (9.8%), respectively. Age ( P = .007, B = 0.002), and preoperative CDVA ( P < .001, B = −0.405) were significantly associated with CDVA improvement. The outcome in eyes with lower myopia was significantly better than in eyes with hyperopia (0.054 logMAR difference; P = .016) or high myopia (0.036 logMAR difference; P = .002). Moderately amblyopic eyes had significantly better visual outcomes than mildly amblyopic eyes (0.038 logMAR difference; P = .001). No significant difference was found between PRK and LASIK ( P = .262). Conclusions : Laser vision correction, regardless of the type of procedure (LASIK or PRK) might improve CDVA in a large portion of amblyopic patients. Improvement was greater in younger patients, eyes with lower initial CDVA, and eyes with lower myopia.